Gender Equality in the Animated Film Calamity, une Enfance de Martha Jane Cannary: A Study of Simone de Beauvoir's Existentialist Feminism - Artanti, Yeni; Adistya, Amelia Putri; Mustofa, Andi; Kusumaningtyas, Vita; Iswatiningsih, Daroe (Universitas Muhammadiyah Malang, 2025)
This research begins with the phenomenon of gender inequality that is still represented in the media, including animated films that often depict women in subordinate positions. The animated film Calamity, une Enfance de Martha Jane Cannary was chosen as the object of study because it features a female character who challenges patriarchal social norms in the 19th century. The purpose of this research is to analyze and understand the representation of gender equality in the film through the perspective of Simone de Beauvoir's existentialist feminism, by highlighting the female character's struggle to fight patriarchal structures and achieve existential freedom. The method used is descriptive qualitative with a content analysis approach, through observation, documentation, and note-taking techniques. Data were obtained from scenes, dialogues, and visual symbols that depict the main character's struggle to become an independent subject. The results show that the film displays three main forms of equality—namely, working, acquiring knowledge, and rejecting stereotypes—and shows the transformation of the female character from a passive object to an agent of change. In addition, the film also critiques forms of gender injustice such as stereotypes, subordination, and symbolic violence. In conclusion, Calamity is not only a medium of entertainment but also a visual representation of women's struggle to gain existence and equality in the midst of a patriarchal culture.